Prediction of postoperative intensive care unit admission with artificial intelligence models in non-small cell lung carcinoma - Isik, Gizem Ozcibik; Kilic, Burcu; Ersen, Ezel; Kaynak, Mehmet Kamil; Turna, Akif; Ozcibik, Onur Sefa; Yildirim, Tulay; Kara, Hasan Volkan (BMC, 2025)
BackgroundThere is no standard practice for intensive care admission after non-small cell lung cancer surgery. In this study, we aimed to determine the need for intensive care admission after non-small cell lung cancer surgery with deep learning models.MethodsThe data of 953 patients who were operated for non-small cell lung cancer between January 2001 and 2023 was analyzed. Clinical, laboratory, respiratory, tumor's radiological and surgical features were included as input data in the study. The outcome data was intensive care unit admission. Deep learning was performed with the Fully Connected Neural Network algorithm and k-fold cross validation method.ResultsThe training accuracy value was 92.0%, the training F1 1 score of the algorithm was 86.7%, the training F1 0 value was 94.2%, and the training F1 average score was 90.5%. The test sensitivity value of the algorithm was 67.7%, the test positive predictive value was 84.0%, and the test accuracy value was 85.3%. Test F1 1 score was 75.0%, test F1 0 score was 89.5%, and test F1 average score was 82.3%. The AUC in the ROC curve created for the success analysis of the algorithm's test data was 0.83.ConclusionsUsing our method deep learning models predicted the need for intensive care unit admission with high success and confidence values. The use of artificial intelligence algorithms for the necessity of intensive care hospitalization will ensure that postoperative processes are carried out safely using objective decision mechanisms.
Keywords: Artificial Intelligence; Intensive care unit; Non-small cell lung cancer; CANCER; SURGERY; VALIDATION; THERAPY; CLASSIFICATION; NEOADJUVANT; MORBIDITY; RESECTION; RISK; Research & Experimental Medicine